Embryogenesis and Behaviour Development of Asian Catfish Silurus triostegus Heckel From Fertilization to Hatching - Aldoori, T.Y.; Daham, H.M.D.; Jaza’a, T.F.; Mohammed, M.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
For the first time in Iraq, this study presented a putj;uance to ti the main embryological development phases of the Asian catfish Silurus triostegus .Embryological morphological illustrations and behaviour remark have been given. It was found that eggs of this species are of Telolecithal type. Two hours after fertilization of the fi rst cleavage took place , it became taster until the 64 cells stage, afslowed down . In 4 hours the eggs reached the morula stage while gastrula stage achieved within 9 hours. Separation of head and tail commence at 25 hours . First, heart pulssing was observed at 35 hourswhile blood flow started 8 hours later . Chromatophores appeard at 52 hours . As for the barbeles , the first pair became distinct at 58 hours and at 64 hours. they became three pa ires . Highest Percentage of hatching occurred between 70 to 75 hours and completed at 96 hours after ftertil ization.